Downregulation of ATXN3 Enhances the Sensitivity to AKT Inhibitors (Perifosine or MK-2206), but Decreases the Sensitivity to Chemotherapeutic Drugs (Etoposide or Cisplatin) in Neuroblastoma Cells - Gong, Baocheng; Zhang, Jinhua; Hua, Zhongyan; Liu, Zhihui; Thiele, Carol J.; Li, Zhijie (Frontiers in Oncology, 2021)
Background Chemotherapy resistance is the major cause of failure in neuroblastoma (NB) treatment. ATXN3 has been linked to various types of cancer and neurodegenerative diseases; however, its roles in NB have not been established. The aim of our study was to explore the role of ATXN3 in the cell death induced by AKT inhibitor (perifosine or MK-2206) or chemotherapy drugs (etoposide or cisplatin) in NB cells. Methods The expressions of ATXN3 and BCL-2 family members were detected by Western blot. Cell survival was evaluated by CCK8, cell confluence was measured by IncuCyte, and apoptosis was detected by flow cytometry. AS and BE2 were treated with AKT inhibitors or chemotherapeutics, respectively. Results Downregulation of ATXN3 did not block, but significantly increased the perifosine/MK-2206-induced cell death. Among the BCL-2 family members, the expression of pro-apoptotic protein BIM and anti-proapoptotic protein Bcl-xl expression increased significantly when ATXN3 was down-regulated. Downregulation of BIM protected NB cells from the combination of perifosine/MK-2206 and ATXN3 downregulation. Downregulation of ATXN3 did not increase, but decrease the sensitivity of NB cells to etoposide/cisplatin, and knockdown of Bcl-xl attenuated this decrease in sensitivity. Conclusion Downregulation of ATXN3 enhanced AKT inhibitors (perifosine or MK-2206) induced cell death by BIM, but decreased the cell death induced by chemotherapeutic drugs (etoposide or cisplatin) via Bcl-xl. The expression of ATXN3 may be an indicator in selecting different treatment regimen.